2018
DOI: 10.1186/s13089-018-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined lung and brain ultrasonography for an individualized “brain-protective ventilation strategy” in neurocritical care patients with challenging ventilation needs

Abstract: When intracranial hypertension and severe lung damage coexist in the same clinical scenario, their management poses a difficult challenge, especially as concerns mechanical ventilation management. The needs of combined lung and brain protection from secondary damage may conflict, as ventilation strategies commonly used in patients with ARDS are potentially associated with an increased risk of intracranial hypertension. In particular, the use of positive end-expiratory pressure, recruitment maneuvers, prone pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(55 reference statements)
1
14
0
1
Order By: Relevance
“…This latter point is of extreme importance, as neurological complications are common in mechanically ventilated critically ill patients with COVID-19 [ 17 , 18 ] and may lead to impaired cerebral hemodynamics [ 17 , 19 ]. Furthermore, respiratory rescue therapies may have detrimental effects on brain physiology, especially in the early phases after application, when the major hemodynamic and respiratory changes occur; therefore, their application in brain-injured patients outside of the COVID-19 pandemic is currently debated [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This latter point is of extreme importance, as neurological complications are common in mechanically ventilated critically ill patients with COVID-19 [ 17 , 18 ] and may lead to impaired cerebral hemodynamics [ 17 , 19 ]. Furthermore, respiratory rescue therapies may have detrimental effects on brain physiology, especially in the early phases after application, when the major hemodynamic and respiratory changes occur; therefore, their application in brain-injured patients outside of the COVID-19 pandemic is currently debated [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, mean ONSD increased significantly upon prone positioning and upon a PEEP application of 8 cm H 2 O [20]. For this reason, if a patient has brain injury and requires mechanical ventilation, particular care is recommended not only for lung protection but also for brain protection [11]. On the other hand, hypercarbia is frequently seen in patients in our intensive care practices.…”
Section: Discussionmentioning
confidence: 62%
“…Ultrasonographic images should be obtained with appropriate techniques according to new Optic Nerve Sonography Quality Criteria [8]. Recent studies suggest that daily monitoring of ONSD measurement by USG can be useful not only for the determination of increased ICP but also for evaluating the neurological prognosis of the patients [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of positive end-expiratory pressure (PEEP), recruitment maneuvers and prone position in order to prevent atelectasis in the intraoperative period may cause undesirable effects on cerebral physiology by decreasing cerebral venous return and mean arterial pressure. In addition, lung-sparing ventilation targets (airway plateau pressure <28-30 cmH 2 0, driving pressure <14 cmH 2 0 or delta-transpulmonary pressures <10-12 cmH 2 0) may cause hypercarbia, leading to changes in intracranial pressure [1]. It has been shown that continuous PEEP applications lower cerebral blood flow and cerebral perfusion pressure both in healthy volunteers and patients with cerebral damage [2].…”
Section: Introductionmentioning
confidence: 99%
“…PEEP opens collapsed alveoli, improving oxygenation. In this way, end-expiratory alveolar collapse is prevented, intrapulmonary shunting is reduced, functional residual capacity is increased, and the risk of developing complications such as ventilator mediated pneumonia or pulmonary damage is decreased in patients under general anesthesia [3]. The optic nerve, which is part of the central nervous system, is surrounded by a subarachnoid space containing the dural sheath and cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%